Soft-magnetic-body-containing photocurable resin and method for forming soft-magnetic-body-containing photocurable resin on a substrate
Patent Information
- Application Number
- CN202580003954.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-03
- Publication Date
- 2026-10-16
AI Technical Summary
[0024] With the structure described above, the present invention can obtain a soft magnetic material powder (e.g., iron) mixed in the resin of the adhesive, and also ensures that the resin cured after mixing the elastic soft magnetic material powder can form a magnetic layer, providing a range of ratios in which the substrate and the magnet can be sufficiently attracted. Furthermore, a method for forming a photocurable resin containing a soft magnetic material on a substrate can be provided. When the photocurable resin containing a soft magnetic material is sprayed onto the substrate, by curing a portion of the adhesive adhering to the substrate before moving the spray window away from the substrate, the spraying shape of the resin can be preserved, and the spraying amount can be appropriately managed based on checking the distance between the sprayed resin particles.
Smart Images

Figure CN122935567A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a photocurable resin containing a soft magnetic material and a method for forming the photocurable resin containing a soft magnetic material on a substrate. Background Technology
[0002] Car seat cushions are typically manufactured by attaching a cover to the body-contacting side of a foam pad, which is formed through molding by injecting polyurethane raw material into a mold and allowing it to foam within the mold. During molding, a fabric-like substrate is pre-positioned within the mold, forming the back side of the foam pad. The resulting foam pad has a structure in which polyurethane is formed on the substrate, reinforcing the polyurethane. In subsequent seat assembly processes, the seat cushion formed by attaching the cover to the now durable foam pad becomes easier to handle.
[0003] During the molding process, a mold with a shape that mimics the shape of a seat cushion on one side of the substrate and a mold with a shape corresponding to the surface side of the manufactured seat cushion are used in combination. The substrate is installed and used by covering the mold. Soft magnetic bodies pre-installed at multiple locations on the substrate are attracted by magnets inserted into the mold, and the substrate is fixed to the mold during the foam pad forming process, such as polyurethane foam pad formation.
[0004] Patent Document 1 discloses the following technology: When a foamed synthetic resin pad body (foam pad in this invention) used in chairs and furniture such as seats and furniture in vehicles, ships, and airplanes is integrally formed with an embedded part such as reinforcing fabric (substrate in this invention), the embedded part can be fixed to the molding mold by adsorbing the magnetic layer on the surface of the pre-formed embedded part to a magnet disposed in the molding mold, which is a forming mold.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent Application Publication No. 2016-036463 Summary of the Invention
[0008] The technical problem that the invention aims to solve
[0009] In Patent Document 1, an adhesive containing powders such as iron and nickel is applied to an imprinting surface, transferred to an embedded part, and then cured to form a magnetic layer. Various synthetic polymers, resins, and photocurable resins, such as synthetic rubber, can be used as the adhesive. However, the mixing ratio of iron and nickel, the amount applied to the embedded part, and the characteristics (magnetic flux density, etc.) of the magnet mounted on the molding die are not disclosed. If the mixing ratio of the metal powders is low, the attraction to the magnet is weak; if the number of magnets and magnetic layer areas in the molding die is increased, the embedded part cannot be fixed to the molding die. If the mixing ratio of the metal powders is excessively increased, the viscosity of the adhesive material increases, resulting in poor sprayability and transferability, and reduced elasticity after curing. Therefore, it is necessary to keep the mixing ratio of the metal powders within an appropriate range and apply an appropriate amount to the reinforcing fabric.
[0010] Therefore, the object of the present invention is to obtain a range of ratios in which a soft magnetic material powder (e.g., iron) mixed in a resin of an adhesive is also ensured, while also ensuring an elastic magnetic layer (the magnetic layer in Patent Document 1. A magnetic layer formed by mixing the resin and the soft magnetic material powder (hereinafter, sometimes simply referred to as soft magnetic material) and curing it, the same applies below), and whereby the ratio of the substrate to which the magnetic layer is formed can be sufficiently attracted to a magnet is provided. Furthermore, the object is to provide a method for forming a photocurable resin containing a soft magnetic material on a substrate, wherein when an adhesive composed of a photocurable resin mixed with a soft magnetic material (hereinafter referred to as a photocurable resin containing a soft magnetic material) is sprayed onto a reinforcing fabric (hereinafter referred to as a substrate), by curing a portion of the adhesive adhering to the substrate before moving the spraying window away from the substrate, the spraying shape of the resin can be preserved, and the spraying amount can be appropriately managed based on checking the distance between the sprayed resins.
[0011] Technical solutions for solving technical problems
[0012] To address the aforementioned technical problems, the present invention provides the following solutions.
[0013] As a first invention, a light-curable resin containing a soft magnetic material is provided. It comprises polymerization raw materials, crosslinking agents, photoinitiators and soft magnetic powder, wherein the polymerization raw materials comprise at least urethane oligomers having acryloyl groups and / or epoxy groups, and the soft magnetic powder comprises 50% to 75% by weight.
[0014] As a second invention, a light-curable resin containing a soft magnetic material is provided, based on the first invention, wherein the crosslinking agent is 2-hydroxypropyl methacrylate.
[0015] As a third invention, a light-curing resin containing a soft magnetic body, based on any one of the first or second inventions, is provided, further comprising a reaction-promoting additive.
[0016] As a fourth invention, a light-curable resin containing a soft magnetic material is provided, based on any one of the first to third inventions, wherein the viscosity of the polymer raw material contained in the resin before light curing is measured by a type B viscometer to be 1,000 to 500,000 mPascals seconds at a rotation speed of 0.6 rpm or less.
[0017] As a fifth invention, a method based on any one of the first to fourth inventions is provided. The viscosity of the polymer raw materials contained in the resin before photocuring was measured using a type B rotational viscometer. The viscosity at 6 rpm was above 40,000 mPascals second and below 44,000 mPascals second, and the viscosity at 12 rpm was above 30,000 mPascals second and below 34,000 mPascals second. This was for photocurable resins containing soft magnetic materials.
[0018] As a sixth invention, a method for forming a photocurable resin containing a soft magnetic material on a substrate is provided, which comprises: The filling step involves filling the cylinder with the light-curable resin containing a soft magnetic material, as described in any one of the first to fifth inventions. In the spraying step, the light-curing resin containing soft magnetic material is sprayed onto the substrate through multiple spray windows located at the front end of the cylinder until it penetrates to the back of the substrate. The interval inspection step involves checking the intervals between the sprayed patterns of the light-cured resin containing soft magnetic materials; and The good or bad determination step is to determine the good or bad quality of the sprayed product through an interval inspection step.
[0019] As the seventh invention, a method based on the sixth invention is provided.
[0020] The substrate is a nonwoven fabric composed of polyester fibers, with a thickness of 0.5 mm to 50 mm and a unit area weight of 50 g / m². 2 Above and 200g / m 2 The following are methods for forming nonwoven fabrics with light-curable resins containing soft magnetic materials on substrates.
[0021] As the eighth invention, a method for forming a photocurable resin containing a soft magnetic material on a substrate is provided, based on any one of the sixth or seventh inventions. Following the ejection step, it further includes: The step of irradiating the back side of a photocurable resin containing a soft magnetic material sprayed onto a substrate with curing light; and The retraction step, following the irradiation step, involves retracting the ejection window upwards toward the light-cured resin containing the soft magnetic material. Following the retreat step, there is a curing step in which a light-curing resin containing a soft magnetic material, ejected from the substrate, is irradiated with curing light from above and / or below.
[0022] As the ninth invention, a method based on any one of the sixth to eighth inventions is provided. A method for forming a photocurable resin containing a soft magnetic material on a substrate in the spraying step, wherein the weight of the photocurable resin containing a soft magnetic material sprayed onto the substrate is in the range of 0.10 g to 0.25 g.
[0023] The effects of the invention
[0024] With the structure described above, the present invention can obtain a soft magnetic material powder (e.g., iron) mixed in the resin of the adhesive, and also ensures that the resin cured after mixing the elastic soft magnetic material powder can form a magnetic layer, providing a range of ratios in which the substrate and the magnet can be sufficiently attracted. Furthermore, a method for forming a photocurable resin containing a soft magnetic material on a substrate can be provided. When the photocurable resin containing a soft magnetic material is sprayed onto the substrate, by curing a portion of the adhesive adhering to the substrate before moving the spray window away from the substrate, the spraying shape of the resin can be preserved, and the spraying amount can be appropriately managed based on checking the distance between the sprayed resin particles. Attached Figure Description
[0025] Figure 1 This is an explanatory diagram of the structure of a car seat.
[0026] Figure 2 This is a graph showing the weight percentage (%) of iron powder and viscosity in the photocurable resin containing soft magnetic material of the present invention.
[0027] Figure 3 This is an illustrative diagram illustrating the manufacturing process of seat inserts and cushions for automotive seats.
[0028] Figure 4 This is a flowchart illustrating the magnetic body installation process according to Embodiment 6 of the present invention.
[0029] Figure 5 This is an example of multiple ejection windows at the front end of the cylinder block of the present invention.
[0030] Figure 6 This is a schematic cross-section of the photocurable resin containing a soft magnetic material of the present invention after it has been sprayed onto the surface of a substrate. Figure 1 .
[0031] Figure 7 This is a schematic cross-section of the photocurable resin containing a soft magnetic material of the present invention after it has been sprayed onto the surface of a substrate. Figure 2 .
[0032] Figure 8 These are photographs and schematic diagrams of resin images after the photocurable resin containing soft magnetic material of the present invention has been sprayed onto the surface of a substrate.
[0033] Figure 9 This is a schematic diagram showing an example of a pattern void inspection area of the photocurable resin containing a soft magnetic material of the present invention sprayed onto the surface of a substrate.
[0034] Figure 10 This is a flowchart illustrating the magnetic body installation process according to Embodiment 7 of the present invention.
[0035] Figure 11 This is an explanatory diagram of the magnetic body installation process according to Embodiment 8 of the present invention.
[0036] Figure 12 This is a flowchart illustrating the magnetic body installation process according to Embodiment 9 of the present invention.
[0037] Figure 13 This is a flowchart illustrating the magnetic body installation process according to Embodiment 9 of the present invention.
[0038] Figure 14 This is a graph showing the weight ratio (%) of iron powder and the adsorption force (N) in the photocurable resin containing soft magnetic material of the present invention.
[0039] Figure 15 This is a graph showing the weight ratio (%) of iron powder and the relative permeability in the photocurable resin containing soft magnetic materials of the present invention.
[0040] Figure 16 This is a graph showing the weight ratio (%) of iron powder and the opening ratio in the photocurable resin containing soft magnetic material of the present invention. Detailed Implementation
[0041] The embodiments of the present invention will be described below. It should be noted that the present invention is not limited to these embodiments and can be implemented in various ways without departing from its spirit. The descriptions of the invention's structure and the reference numerals in the accompanying drawings are represented by four digits, with the top two digits indicating the drawing number and the bottom two digits indicating the number inherently assigned to each part.
[0042] In this specification, the following example will be used: a substrate consisting of a nonwoven fabric to which a magnetic layer formed by curing the resin containing a soft magnetic material of the present invention is used as a substrate for a foam pad for cushioning a car seat, using the method of forming the resin containing a soft magnetic material on a substrate.
[0043] It should be noted that the application of this invention is not limited to automobile seats. It can also be applied to other applications besides automobiles, such as seats for motorcycles, forklifts and other handling equipment, construction machinery such as power excavators, agricultural machinery such as combine harvesters, passenger transport systems such as trams and buses, seats for ships, airplanes, spacecraft and other vehicles, sofas, gaming chairs and office chairs, wheelchair seats, etc. Besides seats, it can also be applied to the substrates of helmet cushioning materials, sound insulation materials, and heat insulation materials. Furthermore, a substrate composed of a nonwoven fabric with a magnetic layer attached using the resin of this invention and the method for forming the resin on a substrate can be applied as a substrate monomer in automobile sound insulation and vibration damping insulators (insulators for dashboards, floors, doors, etc.) without forming a foam pad.
[0044] Furthermore, it can be used not only to attach a magnetic layer to non-woven fabrics, woven fabrics, or thin film sheets as substrates for magnet adsorption, but also as inks and coatings. Information (e.g., object identification information, object attribute information (material, place of origin, manufacturer, manufacturer, manufacturing date, manufacturing batch, product name, model, owner, warranty period, usable life, etc.), shipper and recipient information, etc.) can be included in a predetermined pattern formed by the ink using the resin of the present invention on the surface of a product or packaging box. For example, it can be used to form barcodes or QR codes on the surface of a product or packaging box using ink using the resin of the present invention. Furthermore, when the formed barcode or QR code is covered from above with ink of the same color as the ink, it cannot be read by visual or optical readers. By concealing the formation site of the barcode or QR code in appearance and using a magnetic reader for reading, the possibility of others reading the code's content can be reduced.
[0045] Alternatively, by applying a coating using the resin of this invention to the walls of a building, posters can be attached with magnets, magnetic hooks can be installed, or various components can be mounted with magnets. When attaching iron plates to a wall, the wall needs to be reinforced to bear the weight of the iron plates. However, a light-cured resin layer containing soft magnetic materials, formed by applying a coating using the resin of this invention, is not as heavy as an iron plate, eliminating the need for wall reinforcement. It should be noted that even with soft magnetic materials, this invention, which contains powdered materials such as paints containing magnetized soft magnetic materials like ferrites with high coercivity, can be used as a coating material for structures made of soft magnetic materials, such as automobile bodies (which retain some soft magnetism in stainless steel), steel structures like bridges and storage tanks. In this case, since the paint is difficult to peel off from the surface of the structure, highly durable coatings can be applied.
[0046] <Seating: Structure>
[0047] use Figure 1 The structure of car seats will be explained. Car seats are divided into front seats and rear seats in terms of shape, but they are roughly the same in structure, consisting of approximately three parts. These three parts are as follows... Figure 1 As shown, there is a seat surface (0101) for a person to sit on (also called a seat cushion), a backrest (0102) for a person to lean back (also called a seat back), and a headrest (0103) installed on the upper part of the backrest.
[0048] In addition, such as Figure 1 As shown, the seat has a foam pad (0106) formed using foamed urethane resin or the like directly mounted on a substrate (0105) relative to a tubular frame (0104) composed of metal tubes and springs. A cover (0107) is then attached to the foam pad (0106) by means of adhesive bonding or other methods.
[0049] exist Figure 1 On the left side, Figure 1 A cross-section of a portion of the backrest is shown within the circle. Between the seat frame (0104) and the foam pad (0106) made of foamed urethane resin or the like, a substrate (0105) formed of non-woven fabric, woven cloth, or a thin film sheet is disposed to prevent frictional wear between the foam pad (0106) and the frame (0104) due to vehicle swaying and occupant movement during travel. A skin (0107) is attached to the surface of the foam pad (0106) that comes into contact with the occupant, which helps improve the durability and appearance of the foam pad (0106).
[0050] <Summary of Embodiment 1> Mainly claims 1
[0051] The photocurable resin containing a soft magnetic material used to form a magnetic layer on a substrate such as a nonwoven fabric is composed of a polymerization raw material, a crosslinking agent, a photoinitiator, and a soft magnetic material powder. The polymerization raw material contains at least a urethane oligomer having an acryloyl group and / or an epoxy group, and the soft magnetic material powder is 50% to 75% by weight.
[0052] <Effective Method 1: Light-curable resin>
[0053] "Photocurable resin" must be "polymerization raw material" and "photoreaction initiator", and may further include "crosslinking agent", "reaction promoting additive", "filler", and "stabilizer", etc.
[0054] <Implementation Method 1: Photocurable Resin: Curing Mechanism>
[0055] When the "photocurable resin" is irradiated with light of a specified wavelength, a "photoinitiator" corresponding to the "polymerization raw material" generates free radicals or cations. These free radicals or cations react with acryloyl groups or epoxy groups in the polymerization raw material molecules, causing the C=C double bond of the acryloyl group to break and polymerize at the same site as other polymerization raw material molecules, or causing the epoxy group to open its ring and polymerize at the same site. The "crosslinking agent," also possessing acryloyl groups or epoxy groups, can polymerize via the free radicals or cations generated by the photoinitiator, binding with the broken or ring-opened sites in the polymerization raw material molecules to form a three-dimensional mesh-like polymer structure. "Reaction-promoting additives" enhance the efficiency of the photoinitiator, allowing the curing reaction to proceed faster and more effectively. By mixing "fillers" into the resin, the amount of resin used can be reduced. Furthermore, adding fillers can reduce resin shrinkage and expansion. "Stabilizers" are added for heat stabilization, preventing yellowing and cracking caused by light.
[0056] <Effective Method 1: Photocurable Resin: Raw Material for Polymerization>
[0057] "Polymerization raw materials" are substances that form the main skeleton of the cured UV-curable resin. Polymerization raw materials are monomers and / or oligomers. Among these polymerization raw materials, UV-curable acrylate resins with acryloyl groups (e.g., urethane acrylates, polyester acrylates, methyl acrylate, ethyl acrylate, butyl acrylate, etc.), methacrylic resins with methacrylic groups where the H in the acrylate group is replaced by CH3 (e.g., polymethacrylate, polymethacrylic acidester), UV-curable epoxy resins, vinyl ester resins, epoxy acrylates, etc., can be used.
[0058] <Effective Method 1: Photocurable Resin: Photoreaction Initiator>
[0059] A photoinitiator receives curing light (e.g., ultraviolet or visible light within a specific wavelength range) and generates and releases free radicals or cations from its molecules for reaction with the polymerization raw materials. If the polymerization raw materials used are acrylate-based, a photoinitiator for acrylate resins is used. If the polymerization raw materials used are epoxy-based, a photoinitiator for epoxy resins is used.
[0060] When acrylate resins are exposed to ultraviolet light using photoinitiators (e.g., benzophenone-based, acetophenone-based, benzoin ether-based, thioxanone-based), free radicals are generated, which then polymerize by reacting with the C=C bonds of the acrylate. Epoxy resins, when exposed to ultraviolet light using photoinitiators (e.g., sulfonium salts such as diphenylsulfonium salts, iodonium salts of triphenyliodonium salts), generate cations (acids), which then polymerize by reacting with epoxy groups.
[0061] <Effective Method 1: Photocurable Resin and Crosslinking Agent>
[0062] A "crosslinking agent" is added to connect the molecules of the polymer raw materials to form a three-dimensional mesh structure, thereby improving the curing degree, strength, or durability of the resin. As a crosslinking agent, 2-hydroxypropyl methacrylate is used when polymer raw materials with acryloyl groups are used, and polyisocyanate is used when polymer raw materials with epoxy groups are used. The specific names of the substances used as crosslinking agents will be explained in Embodiment 2 described later.
[0063] <Effective Method 1: Photocurable Resin: Reaction Accelerator Additive>
[0064] "Reaction-promoting additives" facilitate the reaction in which a photoinitiator generates and releases free radicals and cations. For example, they absorb light of wavelengths other than those absorbed by the photoinitiator, causing energy to shift towards the photoinitiator within a distance of 10 nm (Foster mechanism), or they exchange electrons in the excited state within the reaction-promoting additive with electrons in the photoinitiator (Dexster mechanism), directly causing energy shift. The photoinitiator molecules that receive the shifted energy generate and release active species (free radicals or cations). Alternatively, the reaction-promoting additive receives light of the same and / or different wavelengths as the photoinitiator, generating and releasing the same type of active species (free radicals or cations) as the photoinitiator. Thus, by increasing the amount of these active species generated and released, the polymerization of raw materials for polymerization is promoted.
[0065] When using monomers and / or oligomers with acryloyl groups as raw materials for polymerization, reaction-promoting additives can be triphenylamine (TPA) and dimethylamine (DMA). Alternatively, when using monomers and / or oligomers with epoxy groups as raw materials for polymerization, reaction-promoting additives can be methyldiethanolamine (MDEA) and dimethylamine (DMA). Specific names of the substances used as reaction-promoting additives will be explained in Embodiment 3 described later.
[0066] <Effective Method 1: Light-curable resin: Curing conditions>
[0067] During the curing of photocurable resins, light suitable for curing the selected resin (e.g., ultraviolet light, UVA (wavelength 315~400nm), visible light above 400nm and below 420nm, visible light, etc.) is used, and the required cumulative light intensity (mJ / cm²) is determined. 2 The cumulative light intensity is the sum of light intensity calculated by multiplying "light intensity" by "time". The unit for the cumulative light intensity required to cure the resin per unit area is mJ / cm², as described above. 2 In acrylate resins that respond quickly to light, it is particularly preferred to use cured, elastic urethane acrylate oligomers as raw materials for polymerization. In photocurable resins using these urethane acrylate oligomers as polymerization raw materials, the cumulative light intensity is typically 1000~3000 mJ / cm² as the curing light. 2 When using UVA (or visible light above 400nm and below 420nm), curing occurs within a few seconds. When using a light source with low light intensity, the required curing time is extended because the specified cumulative light intensity is not reached within a short time.
[0068] In this application specification, an ultraviolet-curable resin is used as an example of a photocurable resin, but the same effect can be obtained even if a resin that is cured using light of other wavelengths such as visible light is used (this is also the case in other embodiments). The main difference lies in adjusting the wavelength of the light used for curing, by adjusting the photoinitiator and selecting a photoinitiator that generates free radicals and / or cations at the desired wavelength.
[0069] The glass transition temperature and / or melting point of the photocurable resin is preferably 150°C or higher. When forming a magnetic layer on a substrate using the resin of this embodiment of the invention, it is placed near the location where the resin causing the foaming reaction of foamed urethane or similar resins is located, in the formation of a foam pad for a seat cushion or a foamed material for thermal and sound insulation. For example, during the foaming of the foamed urethane, temperatures may reach approximately 60°C to 150°C. When the magnetic layer is exposed to such temperatures, if the photocurable resin melts and adheres to the mold, it may adhere to the next substrate and become contaminated. Therefore, a resin that does not melt at the temperature during the foaming reaction of such resins is preferred.
[0070] <Implementation Method 1: Soft Magnetic Powder>
[0071] In this invention, a magnetic layer is formed on a substrate made of nonwoven fabric or the like. The soft magnetic powder added to the photocurable resin can be powders of iron, nickel, cobalt, etc. Iron powder, which is readily available and inexpensive, is most preferably used as the soft magnetic powder. In the embodiments described in this specification, iron powder is used as an example of the soft magnetic powder, but the same effect can be obtained by using other known soft magnetic materials such as nickel and cobalt.
[0072] <Implementation Method 1: Weight Ratio of Soft Magnetic Powder>
[0073] In the photocurable resin containing a soft magnetic material of the present invention, the weight ratio of the soft magnetic material powder to the photocurable resin is 50 wt% or more and 75 wt% or less. The range of the weight ratio of the soft magnetic material powder was determined by evaluating and studying the viscosity, cured state, magnetic attraction, BH characteristics, relative permeability, and aperture ratio (defined below) of the mixture containing the iron powder in the photocurable resin, using readily available iron powder as an example of a soft magnetic material powder.
[0074] <Implementation Method 1: Iron powder weight ratio: viscosity>
[0075] Based on the evaluation results of the viscosity of the photocurable resin mixed with iron powder, the upper limit of the weight ratio of iron powder in the photocurable resin containing soft magnetic material is first explained. Figure 2 The weight percentage (%) of iron powder in the photocurable resin containing soft magnetic materials is plotted on the horizontal axis (linear representation), and the viscosity of the resin (using a type B viscometer, 0.6 rpm) is plotted on the vertical axis (logarithmic representation). Figure 2 In the figure, black dots represent the viscosity of each iron powder weight percentage (%). The measured viscosity at an iron powder weight percentage of 55 wt% is 86670 mPa. s, at 60wt%, is 93330mPa. s, at 65wt%, is 100000 mPa. s, at 70wt%, is 206700 mPa. s, at 75wt%, is 273300mPa. Furthermore, the dashed line represents the exponential approximation of the viscosity data (represented by black dots) at an iron powder weight ratio of 55–75 wt%. Based on this approximation, the viscosity at 50 wt% is extrapolated to be 53483 mPa. s.
[0076] Next, the lower limit of the iron powder weight ratio will be explained. When spraying a light-curable resin containing a soft magnetic material onto a vertical surface, or when holding the resin in a droplet shape at the tip of a syringe or similar device pointing downwards, the resin viscosity is generally required to be 5000 mPa to prevent it from dripping downwards. Above s. The ease of dripping also depends on the thickness (or height) of the resin after spraying. In this invention, the lower limit of the viscosity of the photocurable resin containing a soft magnetic material before curing is set to 5000 mPa. Above s. As an upper limit, it is set to the maximum possible mixing level of 1,000,000 mPa. s. Preferably, 10000 mPa is more difficult to drip. Above s, capable of mass production of 700,000 mPa Below s. From a viscosity point of view, the range of mixing weight ratios of iron powder (soft magnetic powder) cannot be specified; therefore, the range is determined through other evaluations.
[0077] <Implementation Method 1: Explanation of iron powder weight ratio: Cured state > upper limit of 75wt% or less for iron powder weight ratio>
[0078] In substances obtained by curing a photocurable resin containing iron powder, when the weight ratio of iron powder exceeds 75 wt%, the cured material cannot maintain its elasticity and is prone to cracking when bent. As a substrate for foam pads used in car seats, it is unsuitable for magnetic layers where bending forces may be applied when mounted onto molds used for foam pad formation. Similarly, it is unsuitable for applications where bending forces are applied to the cured magnetic layer (heat-insulating and sound-insulating materials with folded sections, or covers formed on soft sheet substrates that are folded and stored when not in use, etc.). Therefore, the weight ratio of iron powder is set to 75 wt% or less.
[0079] <Effective Method 1: Explanation of Iron Powder Weight Ratio: Adsorption to Magnet > 50 wt% or more of the lower limit of iron powder weight ratio>
[0080] Based on the evaluation results of the adsorption with the magnet, the lower limit of the iron powder weight ratio is explained. The adsorption of the resin obtained by curing the photocurable resin containing the soft magnetic material of the present invention with the magnet is performed to fix and hold the sheet-like substrate from which the resin of the present invention has been sprayed using the magnet. Therefore, if the iron powder weight ratio in the resin is too low, the adsorption force with the magnet is insufficient. The lower limit of the iron powder weight ratio required to hold the substrate was investigated. As a specific example of evaluation, the adsorption force for fixing the substrate as a nonwoven fabric was evaluated using a magnet (surface magnetic flux density of 0.30~0.44T) for substrate mounting provided in a mold for forming a foam pad. The adsorption force needs to be at least 1.5N. This is because, as a substrate for car seats, in the largest rear double seat surface, it is approximately 1.4m × 0.5m = 0.7m. 2 The area. This is because, using the unit area weight range of 50 g / m² described in Embodiment 7 (described later). 2 Above and 200g / m 2 200g / m 2 When the non-woven fabric is used as the base material for the rear seat surface, it can fix 0.75m as long as it has an adsorption force of 1.5N. 2 A nonwoven fabric (weighing 150g) was used to fix the rear seat surface. Ten samples with varying iron powder weight ratios were prepared under each condition, and the adsorption force was measured. Due to potential deviations in the adsorption force measurement, and the possibility of forces causing the nonwoven fabric to shift during the foaming and expansion of urethane and other materials in the foam pad formation, a margin of 2.4N or more was not used as the criterion for judging the quality of the evaluation conditions. Minimizing the number of magnetic layers mounted on the substrate can reduce installation time, material costs, etc.
[0081] In the evaluation of adsorption with magnets, three samples with iron powder weight ratios of 55wt%, 60wt%, and 65wt% were evaluated (refer to...). Figure 9For evaluation, samples were prepared by spraying 0.125 g of a photocurable resin containing a soft magnetic material at each iron powder weight ratio into a 16 mm diameter circle on the surface of a nonwoven fabric substrate and allowing it to cure. Based on the evaluation results under the condition of an iron powder weight ratio of 3, a linear approximation was used as an approximation line based on the three results. When the iron powder weight ratio is greater than 65 wt%, since the amount of soft magnetic material powder that contributes to adsorption to the magnet increases, it can be considered that, as shown by the approximation line, the adsorption force becomes stronger than that of 65 wt% soft magnetic material powder, or the adsorption force saturates relative to the increase in the iron powder weight ratio. This was confirmed by extrapolation using the approximation line for values above 65 wt%. Regarding values less than 55 wt%, it can be considered that the adsorption force decreases as the iron powder weight ratio decreases, so this was also confirmed by extrapolation using the approximation line. At 50 wt% and above, approximately 2.4 N can be calculated, and it is expected that an adsorption force sufficient to maintain the margin can be obtained relative to a baseline of 1.5 N; therefore, the lower limit of the iron powder weight ratio was set at 50 wt%. Preferably, it is 55wt% or higher.
[0082] <Implementation Method 1: Explanation of iron powder weight ratio: BH characteristics, relative permeability > upper limit of 75wt% for iron powder weight ratio>
[0083] Based on the evaluation results of the relative permeability obtained from the measurement of the BH characteristics of samples with varying iron powder weight ratios, the upper limit of the iron powder weight ratio is explained. Samples (50 wt%, 60 wt%, 70 wt%) of iron powder mixed in a photocurable resin with varying weight ratios were prepared as soft magnetic materials, and their BH characteristics were measured. This was to determine an appropriate iron powder weight ratio based on the magnetic properties of the photocurable resin containing the soft magnetic material. The relative permeability was determined from the slope of the BH characteristic curves of each sample. A curve was prepared with the iron powder weight ratio (wt%) on the horizontal axis and the relative permeability on the vertical axis. Figure 10 The approximate line is also shown as a dashed line. When preparing the test specimens, it was impossible to fabricate the shape of the specimens for BH characteristic testing at 75 wt%, so the approximate line was extrapolated from 75 wt%. Based on the measured values, the relative permeability for each iron powder weight ratio was 2.65 at 50 wt%, 3.68 at 60 wt%, and 4.06 at 70 wt%. The relative permeability (reference) at 75 wt% extrapolated from the approximate line was 4.16. The deviation of these relative permeabilities is ±10%, preferably ±5%.
[0084] When iron powder is mixed into resin, the permeability of the resin changes depending on the weight ratio of the iron powder. Generally, in resin monomers that do not contain soft magnetic materials, the relative permeability is close to 1. When iron powder is mixed into the resin, the high responsiveness (magnetization) of the iron powder to a magnetic field is reflected in the overall properties of the material. Therefore, the magnetic resistance of the mixture (photocurable resin containing soft magnetic materials) decreases, and the relative permeability increases. Permeability is an indicator of how easily a magnetic field passes through a material. When the weight ratio of iron powder increases from 50 wt% to 60 wt%, the distance between the iron powder particles dispersed in the resin becomes closer than at lower weight ratios. This makes it easier for the iron powder particles to magnetically bond, thus forming a path (magnetic path) through which the magnetic field continuously passes, and the permeability increases. When the weight ratio of iron powder is further increased, reaching very high levels such as 75 wt% or above, the distance between the iron powder particles decreases, thus enhancing the magnetic interaction between the iron powder particles, and sometimes even allowing them to come into contact. Thus, at high weight ratios, the interaction between iron powder particles becomes dominant, and the magnetization of individual iron powder particles easily saturates, or the magnetic field is difficult to pass through due to the close arrangement of the iron powder, resulting in passivation of the increase in relative permeability. Therefore, the higher the weight ratio of iron powder, the higher the relative permeability of the mixed resin, becoming... Figure 10 That would be the outcome.
[0085] As described above, it can be considered that once the relative permeability increases to around 70 wt%, the increase in relative permeability will be passivated in the region exceeding 75 wt%, even if the weight ratio of iron powder, which is a soft magnetic material, is increased. Therefore, the upper limit of the iron powder weight ratio is 75 wt% or less, preferably 70 wt% or less.
[0086] <Implementation Method 1: Explanation of Iron Powder Weight Ratio: Opening Ratio > 75wt% or less of the upper limit for Iron Powder Weight Ratio>
[0087] When a resin mixed with iron powder is irradiated with curing light, the upper limit of the iron powder weight ratio is explained based on the result of a simplified calculation of the irradiation rate up to the side opposite to the irradiated surface. When irradiating a photocurable resin containing a soft magnetic material with curing light, a simplified estimate is made based on the area ratio of the resin surface where the iron powder, as a soft magnetic material powder mixed in the photocurable resin, does not obstruct the curing light and the light can penetrate to the side opposite to the incident surface. Iron oxide (Fe3O4) is typically formed on the surface of iron powder, which is readily available as a soft magnetic material powder. Iron oxide, as the curing light for photocurable resins, generally has low UVA reflectivity. As an institution to verify the effectiveness of the iron powder weight ratio, the area ratio is estimated as the ratio of the area in the thickness direction of the cured resin where no iron powder particle is disposed to the projected area of the cured resin (hereinafter referred to as the aperture ratio).
[0088] <Implementation Method 1: Iron powder weight ratio: Opening ratio: Prerequisites>
[0089] In the model studied, the specific gravity of the photocurable resin was 1.07, the average particle size of the iron powder was 58 μm, and the density of iron was 7.87 g / cm³. 3 The amount of resin sprayed onto the nonwoven fabric surface was 0.125g and 0.25g, with a sprayed area of 16mm diameter in a circle (2.011cm). 2 The value of ).
[0090] <Implementation Method 1: Steps for estimating the iron powder weight ratio and aperture ratio>
[0091] As an estimation step, for each iron powder weight ratio of 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, and 75wt%, the volume of 1g of the photocurable resin containing the soft magnetic material is calculated, and the density of the resin and the number density of iron powder in the resin (particles / cm³) are calculated respectively. 3 The thickness of the circular plate, when the resin of each iron powder weight ratio is sprayed out in a circular plate shape with a bottom diameter of 16 mm, is calculated using the formula: thickness of circular plate = spraying amount (0.1 g, 0.125 g, or 0.25 g) / density of the resin / bottom area of the circular plate. The integer part of the quotient obtained by dividing the calculated thickness by the diameter of the iron powder (58 μm) is taken as the number of layers of iron powder disposed in the thickness direction. To simplify the calculation, a 1 cm square (area 1 cm²) of the sprayed resin circular plate is defined. 2 Estimate the area.
[0092] <Implementation Method 1: Iron powder weight ratio: Opening ratio: Calculation method of opening ratio>
[0093] Within a 1cm square, a 172×172 grid can be configured, dividing the iron powder, with a diameter of 58μm, into grid-like grids, using one side of each section as the length of the grid. The 172×172 grids partially overlap the calculated number of layers in the thickness direction. The total number of grids (the product of the number of grids per layer and the number of layers) is divided by the number density calculated by weight ratio × (1cm²). 2 The number of iron powder particles is calculated by multiplying the thickness of the ejected circular plate by the number of particles. The probability of placing iron powder on each frame is then calculated. For each frame, a random number is used; if the probability is greater than or equal to the stated probability, then iron powder is placed. For example, in a case where x and y coordinates represent frames within a single layer, and z coordinates represent layers, with a thickness of 3 layers (z=1, 2, 3), if (x...)... n y m ,1) to (x n y m If none of the three layers of (x) are filled with iron powder, then (x) n y mIf the box containing (x) is blank, then (x) n y m ,1) to (x n y m If any one of the layers in (3) is configured with iron powder, then (x n y m The frame is considered to contain iron powder. Taking the thickness direction into account, the number of blank 172×172 frames without iron powder is divided by the number of frames per layer (=172×172) to obtain the aperture ratio. Frames without any iron powder in the thickness direction are those that allow light for curing to pass through.
[0094] <Implementation Method 1: Iron powder weight ratio: opening ratio: results>
[0095] Figure 11 This represents the estimated aperture ratio for each iron powder weight ratio. The graph shows three lines: 0.25g (thin solid line), 0.125g (thick solid line), and 0.1g (thin dashed line). The number of layers in the thickness direction is 0.25g < 0.125g < 0.1g, therefore the aperture ratio is high in this order, with 0.25g having the lowest aperture ratio. At spray amounts of 0.125g and 0.1g, the aperture ratio is above 11% for iron powder weight ratios of 50wt% to 65wt%, indicating a high aperture ratio. Even at an iron powder weight ratio of 75wt%, the aperture ratio is above 4%. On the other hand, at a spray amount of 0.25g, the aperture ratio is above 1.2% from an iron powder weight ratio of 50wt% to 65wt%. At an iron powder weight ratio of 75wt% with a spray amount of 0.25g, the aperture ratio is approximately 0.3%, which is relatively low, but not negligible. In calculations, the opening ratio decreases by one decimal place from 0.02% at 80 wt%. Therefore, from the viewpoint of opening ratio, the upper limit of the iron powder weight ratio is 75 wt%. As mentioned above, when the opening ratio is low, it is preferable to irradiate the curing light from both the back (non-woven fabric side) and the surface of the sprayed resin, as described in the embodiment below. Alternatively, it can be adjusted by increasing the cumulative amount of light irradiated by the curing light.
[0096] The estimated aperture ratio shows that the lower the iron powder weight ratio, the higher the aperture ratio, thus making it easier for the curing light to reach the side opposite to the irradiated surface. The upper limit for the iron powder weight ratio is 75 wt% or less, preferably 70 wt% or less. It should be noted that although the estimate was simplified by assuming the iron powder is arranged in a grid pattern, a hexagonal fine-filling configuration is actually possible, so the aperture ratio may be higher than the above estimate.
[0097] <Implementation Method 1: Iron Powder Weight Ratio: Research Results>
[0098] As evaluated above, the results of the study on the upper and lower limits of the iron powder weight ratio show that the range of soft magnetic material powder contained in the light-curable resin containing soft magnetic materials is 50 wt% or more and 75 wt% or less. Preferably, it is 55 wt% or more and 70 wt% or less, and most preferably 65 wt%. It should be noted that while iron powder was used as an example in the weight ratio study, the same effect can be obtained by using other soft magnetic materials (e.g., nickel, cobalt, etc.).
[0099] <Effects of Implementation Method 1>
[0100] As in Embodiment 1, the light-curing resin containing a soft magnetic material can be used to obtain a magnetic layer with excellent magnet attraction and elasticity after curing by making the weight ratio of iron powder 50 wt% or more and 75 wt% or less.
[0101] <Summary of Embodiment 2> Mainly claims 2
[0102] The photocurable resin containing a soft magnetic material in Embodiment 2 is based on Embodiment 1, and 2-hydroxypropyl methacrylate is used as the crosslinking agent for the photocurable resin containing a soft magnetic material.
[0103] <Implementation Method 2: Crosslinking Agent>
[0104] A "crosslinking agent" is used to form a three-dimensional mesh structure by bonding the monomers and / or oligomers of the polymerization raw materials, thereby improving the curing degree and durability of the resin. By adding functional monomers and oligomers as crosslinking agents, the molecules of the polymerized raw materials are further linked together to form a three-dimensional mesh structure. 2-Hydroxypropyl methacrylate has a methacryloyl group, which, like the acryloyl group, has a C=C bond. In the polymerization reaction, free radicals interact with the C=C bonds of the methacryloyl group of 2-hydroxypropyl methacrylate, crosslinking with the molecules of the urethane oligomer. In the photocurable resin containing a soft magnetic material of Embodiment 1, 2-hydroxypropyl methacrylate is used as the crosslinking agent for the resin, which contains urethane acrylate oligomers with acryloyl groups as polymerization raw materials. This is preferred because it has the effects described below.
[0105] When 2-hydroxypropyl methacrylate (hereinafter referred to as MHP) is used, the following effect is achieved.
[0106] (1) High cross-linking efficiency: MHP has high cross-linking efficiency and can form a porous structure. It functions as a lightweight thermal insulation material and can assist the thermal insulation effect of urethane.
[0107] (2) Durability: Cross-linked polymers have high durability and improved mechanical strength.
[0108] (3) Transparency: The polymer using MHP has high transparency and is suitable for optical applications. Therefore, the transmittance of ultraviolet light is also increased. Thus, during the stage of gradual cross-linking by irradiating curing light containing ultraviolet light, the polymer that is cured first will not hinder the transmission of ultraviolet light.
[0109] (4) Chemical stability: MHP is chemically stable and has excellent weather resistance and chemical resistance.
[0110] Due to these characteristics, it is an excellent crosslinking agent used in this invention.
[0111] As a "crosslinking agent", when acryloyl groups are used as raw materials for polymerization, methacrylic acid-based agents (e.g., 2-hydroxypropyl methacrylate, dimethylaminoethyl methacrylate (DMAEMA), diglycidyl methacrylate (GDMA), etc.) are preferred.
[0112] When the raw material used for polymerization has epoxy groups, the crosslinking agent is preferably a polyisocyanate (e.g., trimellitic acid diisocyanate) or an amine (e.g., diethylaminoethanol (DEAE), triethanolamine).
[0113] <Effects of Implementation Method 2>
[0114] As a crosslinking agent for the photocurable resin containing a soft magnetic material in Embodiment 2, 2-hydroxypropyl methacrylate can be used to further link the polymerized molecules together to form a three-dimensional mesh structure.
[0115] <Summary of Embodiment 3> Mainly claims 3
[0116] The photocurable resin containing a soft magnetic material in Embodiment 3 is based on either Embodiment 1 or Embodiment 2, and further contains a reaction-promoting additive.
[0117] <Implementation Method 3: Reaction-Promoting Additives>
[0118] "Reaction-promoting additives" function as photoinitiators that receive light such as ultraviolet light to further promote photoreaction. When the raw materials for polymerizing photocurable resins containing soft magnetic materials contain acryloyl groups, the photoinitiator facilitates the generation of free radicals for polymerization, thus promoting polymerization. When the raw materials for polymerizing photocurable resins containing soft magnetic materials contain epoxy groups, the photoinitiator facilitates the generation of cations that open the epoxy groups and polymerize them together, thus promoting polymerization.
[0119] <Implementation Method 3: Reaction-promoting additives: specific examples>
[0120] When using monomers and / or oligomers with acryloyl groups as raw materials for polymerization, the following substances may be used as reaction promoters.
[0121] (1) Amines
[0122] Triphenylamine (TPA) and dimethylamine (DMA) are reaction promoters that facilitate the photopolymerization of acrylate resins. These amines enable the polymerization of acryloyl groups to proceed efficiently.
[0123] (2) Phosphine
[0124] Triphenylphosphine (TPP) and trimethylphosphine sometimes promote reactions more effectively than amines in UV curing. They are used in conjunction with photoinitiators to further accelerate the reaction.
[0125] (3) Substituted urea compounds
[0126] Polyurethane acrylate (PUA) is used to enhance the curing reaction of acrylate resins, thereby improving the durability of the cured resin.
[0127] (4) Redox reaction agent
[0128] Peroxides (such as benzoyl peroxide) enhance the effectiveness of photoinitiators through redox reactions in acrylate resins, thereby promoting the curing reaction.
[0129] <Implementation Method 3: Reaction-promoting additives: specific examples>
[0130] When using monomers and / or oligomers with epoxy groups as raw materials for polymerization, the following substances can be used as reaction promoters.
[0131] (1) Amines
[0132] Methyldiethanolamine (MDEA) and dimethylamine (DMA) accelerate the reaction with epoxy groups, promoting the curing process. These amines react directly with epoxy groups to achieve curing.
[0133] (2) Peroxides
[0134] Benzoyl peroxide (BPO) and methyl ethyl ketone peroxide (MEK) are used to promote the photocuring of epoxy resins. These peroxides decompose under ultraviolet light, generating free radicals that accelerate the reaction with epoxy groups.
[0135] (3) Redox reaction agent
[0136] Ascorbic acid (vitamin C) and naphthalene are used in applications where a redox reaction is employed to accelerate the curing of epoxy resins. These agents are reduced through oxidation, which facilitates a rapid curing reaction.
[0137] (4) Metal complexes
[0138] Titanate and chromium complexes are used to accelerate the UV curing reaction of epoxy resins. These metal complexes are activated by UV light, thus accelerating the reaction of the epoxy groups.
[0139] <Effects of Implementation Method 3>
[0140] The photocurable resin containing a soft magnetic material in Embodiment 3 contains a reaction-promoting additive, which enables it to rapidly undergo a curing reaction when exposed to curing light.
[0141] <Summary of Embodiment 4> Mainly claims 4
[0142] The light-curable resin containing a soft magnetic material in Embodiment 4 is based on any one of Embodiments 1 to 3, and is configured such that the viscosity of the polymerization raw material contained in the resin before light curing is 1,000 to 500,000 millipascal-seconds when the rotation speed is 0.6 rpm or less, as measured by a Type B viscometer.
[0143] <Implementation Method 4: Viscosity of Raw Materials for Polymerization>
[0144] The viscosity increases when soft magnetic materials such as iron powder are mixed in, therefore the viscosity of the polymerization raw materials contained in the photocurable resin containing the soft magnetic material before photocuring is also specified. The viscosity of the photocurable resin before mixing the soft magnetic material is roughly equivalent to the viscosity of the polymerization raw materials. This is because, compared to other additives such as crosslinking agents, photoinitiators, and reaction promoters, which are usually liquids, the monomers and oligomers constituting the polymerization raw materials have long molecular chains and large molecular weights, resulting in high viscosity. Consequently, the influence of the polymerization raw materials on the viscosity of the photocurable resin containing the soft magnetic material before photocuring is dominant. If the viscosity of the resin before mixing the soft magnetic material is high, the viscosity after mixing the soft magnetic material will also be high. If a high weight ratio of soft magnetic material powder is desired, the viscosity will become even higher, making mixing difficult. If the viscosity of the polymerization raw materials is below 0.6 rpm on a Type B viscometer and between 1000 and 500000 mPa... If the range of s is specified, then the soft magnetic powders in the weight ratio shown in Embodiment 1 can be mixed to obtain a soft magnetic powder mixture with a viscosity of 5000~1000000 mPa, as described in Embodiment 1. A photocurable resin containing a soft magnetic material, or s or higher. Furthermore, by having the high viscosity described above, for example, when sprayed onto a substrate surface, it prevents liquid from dripping from the tip of the spraying device, allowing the device to move to the next spraying location without taking measures to prevent liquid dripping after spraying. Additionally, even when spraying onto a vertical wall, it prevents liquid dripping after spraying.
[0145] <Effects of Implementation Method 4>
[0146] By mixing a photocurable resin containing the polymerization raw materials of Embodiment 4 with a soft magnetic material, a photocurable resin containing a soft magnetic material as shown in Embodiment 1 can be obtained.
[0147] <Summary of Embodiment 5> Mainly claims 5
[0148] The photocurable resin containing a soft magnetic material in Embodiment 5 is based on any one of Embodiments 1 to 4. The viscosity of the polymer raw material contained in the resin before photocuring is measured by a type B rotational viscometer. The viscosity at 6 rpm is 40,000 mPa·s or more and 44,000 mPa·s or less, and the viscosity at 12 rpm is 30,000 mPa·s or more and 34,000 mPa·s or less.
[0149] In adhesives and similar products sprayed onto walls, there are applications requiring properties where the viscosity decreases upon spraying from the cylinder (when shear force is applied) and increases after the adhesive has settled on the wall (after the shear force is released), making it difficult to drip. This change in viscosity is called thixotropy. Thixotropy is typically measured and compared by, for example, the ratio of viscosity measured using a type B viscometer (e.g., viscosity at 6 rpm / viscosity at 12 rpm).
[0150] <Implementation Method 5: Thixotropy>
[0151] "Thixotropy" refers to "shaking-variability." It is a type of abnormal viscosity. By simply stirring or vibrating the mixture, the gel becomes a flowable sol, but if left to stand, it reverts to its gel properties. It produces hysteresis in the viscosity-displacement stress curve. It was named by Freundlich (HMF) and Peterfi (T.). (Quoted from Iwanami RIP Chemical Dictionary, 5th Edition, Iwanami Shoten, p. 833). In other words, it can be said that when subjected to sustained shear stress, the viscosity gradually decreases, becoming liquid, but when at rest, the viscosity gradually increases, eventually becoming solid.
[0152] When the thixotropy is low when the resin of the present invention is sprayed onto the nonwoven fabric as a substrate, the shape of the sprayed resin is prone to collapse and expand during the period from spraying to light irradiation to cure the resin. Furthermore, as in Embodiment 9 described later, when the photocurable resin containing a soft magnetic material overflows from the spraying window before the spraying window is lowered toward the substrate surface, if the thixotropy is low, the resin sprayed from the spraying window may drip toward the substrate surface and adhere to areas other than the desired location before the spraying window itself approaches the substrate surface. Due to these problems, a specified thixotropy is preferred. The viscosity of the polymerization raw material contained in the photocurable resin before mixing with the soft magnetic material powder was measured using a type B rotational viscometer; the viscosity at 6 rpm was 40000 mPa. s or above and 44000mPa Below s, the viscosity at 12 rpm is 30000 mPa. s or above and 34000mPa The polymerization raw materials (i.e., light-curable resins) are below s. Thus, raw materials containing a specific strength of 40000 mPa are used. s / 34000mPa A photocurable resin with thixotropic polymer raw materials (s=1.176) can be obtained, which contains a soft magnetic material and has a low probability of causing the aforementioned problem.
[0153] <Effects of Implementation Method 5>
[0154] By mixing a thixotropic photocurable resin containing the polymerization raw materials of Embodiment 5 and a soft magnetic material, a photocurable resin containing a soft magnetic material as shown in Embodiment 1 can be obtained. When the photocurable resin containing a soft magnetic material is sprayed onto the substrate, it can prevent the resin from dripping before it is sprayed onto the substrate surface.
[0155] <Summary of Embodiment 6> Primarily refers to claim 6
[0156] A magnetic layer is formed on the surface of a substrate using a photocurable resin containing a soft magnetic material, any one of Embodiments 1 to 5.
[0157] <Implementation Method 6 Structure>
[0158] The method for forming a photocurable resin containing a soft magnetic material on a substrate according to Embodiment 6 comprises a filling step, an ejection step, an interval inspection step, and a good / bad determination step. Before describing the forming method in detail, the manufacturing process of an automobile seat will be described first, taking the substrate as an example.
[0159] <Implementation Method 6: Seat Manufacturing Process>
[0160] Figure 3This represents an example of a car seat. Figure 3 This section primarily describes the substrate manufacturing process and the seat cushion manufacturing process related to the invention of this application. In the seat assembly process of assembling a car seat, relative to... Figure 3 The tube frame manufactured in other processes not shown in the figure is used to install seat cushions such as backrests, seat surfaces, and headrests, thereby assembling the seat. In this application specification, "substrate" refers to the component referred to as the embedding part in Patent Document 1, also known as the seat embedding part. The substrate can be non-woven fabric, woven fabric, film-like sheet, etc. In the following description, the case of using non-woven fabric as the substrate material will be described, but the same effect can be obtained even when using other sheet-like components such as woven fabric and film-like sheet, other than non-woven fabric.
[0161] <Implementation Method 6: Seat Manufacturing Process: Substrate Manufacturing Process: Function of the Substrate>
[0162] On the back side of the foam pad, which is made of foamed urethane or the like, used to form the seat cushion of a car seat, a base material made of non-woven fabric or the like is installed. This base material reinforces the structure of the foam pad, making handling during seat assembly easier. The base material remains useful even after the car is finished. The back side of the foam pad comes into contact with tubes and springs that form the frame of the seat, and rubs against these supporting components due to the swaying of the car during driving and the movement of the occupants' bodies. Therefore, the soft, sponge-like foamed urethane resin or the like is easily damaged. To prevent damage from friction between the foam pad and the supporting components such as the tubes and springs, the base material on the back side of the foam pad is installed as a reinforcing material.
[0163] <Implementation Method 6: Seat Manufacturing Process: Non-woven Fabric Preparation Process>
[0164] Figure 3 The initial step in the substrate manufacturing process shown is the nonwoven fabric preparation step. This involves preparing the nonwoven fabric to be used as material. This can be manufactured in the next step or the nonwoven fabric can be purchased from another company.
[0165] <Effective Implementation 6: Seat Manufacturing Process: Nonwoven Fabric Preparation Process: Nonwoven Fabric Manufacturing Method>
[0166] Examples of raw materials used as substrates will be used to illustrate the manufacturing method of nonwoven fabrics. Nonwoven fabrics can be manufactured using known manufacturing methods and materials. The fibers used as raw materials for nonwoven fabrics are required to remain unchanged at the heating temperature during the foaming reaction when forming a foam pad on the nonwoven fabric in subsequent processes. For example, during the foaming reaction of foamed urethane, the temperature near the center reaches approximately 60-150°C. Therefore, the melting point or softening point of the fibers constituting the nonwoven fabric is preferably 150°C to a sufficiently high 160°C-180°C or higher. For example, known fibers such as polyester, polypropylene, acrylic, and nylon can be used. When using nonwoven fabrics for automotive seats, flame-retardant materials or fibers endowed with flame retardancy are more preferred. The nonwoven fabric is first formed into a pile fabric as a clustered layer of fibers, followed by inter-fiber bonding to bind the fibers together. The pile fabric is formed using any of the known dry, wet, or spunbond methods. The resulting pile fabric combines the fibers using any of the known methods such as needle punching, water weaving, chemical bonding, and thermal bonding.
[0167] <Implementation Method 6: Seat Manufacturing Process: Non-woven Fabric Preparation Process: Non-woven Fabric Specifications>
[0168] The thickness of the nonwoven fabric is 1mm to 5mm. Preferably, it is 1mm to 3mm, more preferably 1.5mm to 2.5mm. Without a certain thickness, the strength relative to friction with the tube and spring is insufficient. If it is too thick, it is difficult to follow the shape of the mold; therefore, the above range is appropriate. The area weight of the nonwoven fabric is 100g / m² when the thickness is 2mm. 2 ~200g / m 2 The preferred value is 120~160g / m 2 If the weight per unit area is small, it can be described as a nonwoven fabric with a coarse mesh, resulting in weaker strength. When the photocurable resin containing soft magnetic material (described later) is sprayed onto the surface of the nonwoven fabric, it may excessively penetrate and expand into the nonwoven fabric, potentially weakening its attraction to the magnet. If the weight per unit area is too large, the rigidity of the nonwoven fabric becomes too high, making it difficult to conform to the shape of the mold. Therefore, the above range is appropriate.
[0169] Alternatively, nonwoven fabrics can be formed by bonding multiple nonwoven fabrics of different specifications together using methods such as needle punching or water jet weaving. For example, a densely packed nonwoven fabric layer with a high weight per unit area can be placed on the side in contact with the tube frame, while a nonwoven fabric layer with a low weight per unit area can be placed on the side where the foam pad is formed. As a result, the densely packed nonwoven fabric layer provides strong friction with the tube frame, while the low weight per unit area nonwoven fabric layer easily penetrates the raw material resin of the foam pad, such as polyurethane resin, resulting in a nonwoven fabric with strong bonding between the nonwoven fabric and the foam pad.
[0170] <Effective Implementation 6: Seat Manufacturing Process: Substrate Manufacturing Process: Non-woven Fabric Forming Process>
[0171] exist Figure 3 In the second step of the substrate manufacturing process, namely the "nonwoven fabric forming process," the nonwoven fabric is processed to form a shape corresponding to the mold used to form the foam pad in subsequent processes. Among the substrates, there are sewing types, where the nonwoven fabric is cut, shaped, and sewn as needed to conform to the mold, and molding types, where it is formed by vacuum forming and stamping. In the latter molding type, for example, thermoplastic fibers are used to maintain the shape that mimics the mold. The nonwoven fabric forming process, as a molding type manufacturing method, has the following steps.
[0172] <Effective Implementation 6: Seat Manufacturing Process: Substrate Manufacturing Process: Non-woven Fabric Molding Process: Installation Steps>
[0173] The "installation step" involves mounting the nonwoven fabric, cut to a specified shape, onto a mold. The mold used in this step has a shape corresponding to the mold used in subsequent steps to form the foam pad. Figure 3 In the example, multiple holes (0313) are provided on the mold (0312), and the nonwoven fabric is formed by vacuum adsorption in the next forming step.
[0174] <Effective Implementation 6: Seat Manufacturing Process: Substrate Manufacturing Process: Non-woven Fabric Molding Process: Molding Steps>
[0175] "Forming step" refers to the steps involved in forming the nonwoven fabric. Figure 3 In one example, forming is performed via vacuum adsorption as described. Although not illustrated, an airtight sheet and bag are covered, for example, by covering the nonwoven fabric and the mold. By venting the space surrounded by the sheet and bag, the nonwoven fabric is sandwiched between the sheet and bag and the mold, forming the shape of the mold. When thermoplastic fibers are used, the nonwoven fabric is heated before forming.
[0176] <Effective Implementation 6: Seat Manufacturing Process: Substrate Manufacturing Process: Non-woven Fabric Molding Process: Disassembly Step>
[0177] The "disassembly step" is the process of removing the molded nonwoven fabric (0323) from the mold (0312). After disassembly, any excess material should be appropriately cut off. The appearance of the molded nonwoven fabric can also be inspected during the disassembly step. This prevents defective products from flowing into the subsequent magnetic assembly process and facilitates the start-up of operations.
[0178] <Embodiment 6: Seat Manufacturing Process: Substrate Manufacturing Process: Magnetic Body Installation Process> Regarding the processes of this invention
[0179] The "magnetic body installation process" is a process in which a magnetic body, which is attached to a magnet disposed on a mold, is installed onto the molded nonwoven fabric when it is mounted onto a mold used in the foam pad forming process of the subsequent seat cushion manufacturing process. In this invention, the method for forming a photocurable resin containing a soft magnetic body on a substrate involves this magnetic body installation process, and therefore will be described in detail after the seat manufacturing process is described.
[0180] <Implementation Method 6: Seat Manufacturing Process: Seat Cushion Manufacturing Process: Foam Cushion Forming Process>
[0181] The "foam pad forming process" is the process of forming a foam pad made of foamed urethane or similar materials on a nonwoven fabric after the seat cushion has been molded. The foam pad forming process consists of the following steps.
[0182] <Effective Implementation 6: Seat Manufacturing Process: Seat Cushion Manufacturing Process: Foam Pad Forming Process: Substrate Installation Step>
[0183] The "substrate installation step" is a process of installing a substrate (0305) with a magnetic layer installed on a molded nonwoven fabric onto the mold 1 (0326). During installation, the magnetic layer (0308) installed at the position corresponding to the magnet set on the mold 1 (0326) is attracted, and the substrate is fixed to the mold 1 (0326). Molded substrates are molded using a mold corresponding to the shape of the mold 1, and can be installed according to the shape of the mold 1. In the case of sewn substrates, the following performance for uneven parts, etc., is worse than that of molded substrates when fixed to the mold 1.
[0184] <Implementation Method 6: Seat Manufacturing Process: Seat Cushion Manufacturing Process: Foam Cushion Forming Process: Mold Assembly Step>
[0185] The "mold assembly step" is a process of combining one or more other molds onto mold 1 (0326) on which the substrate (0305) is mounted. In the example described herein, mold 1 and mold 2 are used together. Combining mold 1 and mold 2 forms a closed space containing the substrate.
[0186] <Effective Implementation 6: Seat Manufacturing Process: Seat Cushion Manufacturing Process: Foam Pad Forming Process: Resin Injection Foaming Step>
[0187] The "resin injection foaming step" is a step in which the raw material for the foam pad is injected into the enclosed space surrounded by mold 1 (0326) and mold 2 (0327), causing it to foam and integrally form a foam pad (0306) with the substrate (0305). Known materials such as urethane resin can be used as the raw material for the foam pad. It should be noted that, in the mold assembly step, the raw material for the foam pad can also be injected into either mold 1 or mold 2 just before mold 1 and mold 2 are assembled.
[0188] <Effective Implementation 6: Seat Manufacturing Process: Seat Cushion Manufacturing Process: Foam Cushion Forming Process: Disassembly Step>
[0189] The "disassembly step" is the step of removing mold 2 (0327) from mold 1 (0326) and removing the formed foam pad (including the substrate) from mold 1 (0326). The foam pad removed from the mold is then subjected to finishing work such as deburring or visual inspection.
[0190] <Implementation Method 6: Seat Manufacturing Process: Seat Cushion Manufacturing Process: Surface Installation Process>
[0191] The "surface installation process" is the process of attaching the skin that will actually come into contact with the rider's body to a foam pad formed on a substrate. An adhesive is applied to the surface of the foam pad, and then the skin is attached.
[0192] <Implementation Method 6: Seat Manufacturing Process: Seat Assembly Process>
[0193] The "seat assembly process" involves attaching the backrest, seat, and headrest of the seat, as described above, to the assembly unit. Figure 3 The process of assembling seats on a tube frame manufactured in a tube frame manufacturing process (not shown) is further carried out in the vehicle assembly process, where the seats are then installed on the vehicle body to complete the vehicle.
[0194] <Implementation Method 6: Description of the Magnetic Body Installation Process>
[0195] In the above-described manufacturing process of the car seat, the following is a detailed description of the installation process using the magnetic material of this application. Figure 4 This describes the steps involved in the installation of magnetic materials. The installation process consists of a filling step, an ejection step, an interval inspection step, and a quality assessment step.
[0196] <Implementation Method 6: Magnetic Body Installation Process: Filling Step>
[0197] The "filling step" is the step of filling the cylinder with the light-curing resin containing a soft magnetic material according to any one of embodiments 1 to 5.
[0198] As a device for ejecting resin from a cylinder with a resin supply chamber, known methods such as cylinders with multiple ejection windows, screen printing, and roller transfer can also be used. In this specification, an example using a cylinder with multiple ejection windows will be described.
[0199] The mixing of the soft magnetic material into the UV-curable resin can be performed by the manufacturer of the UV-curable resin, or by the party installing the magnetic material purchasing the resin and mixing the soft magnetic material. During mixing, thorough stirring is necessary to ensure the soft magnetic material is evenly dispersed in the resin, and care must be taken to prevent air bubbles from remaining in the resin. Furthermore, in locations where the resin is taken from its container from the manufacturer, mixed, or filled, and in production lines near the magnetic material installation process, lighting sources that remove or attenuate wavelengths conducive to curing can be used to ensure that a curing reaction of the UV-curable resin does not occur, and that the increase in viscosity caused by the curing reaction is controlled to an acceptable level for at least 8 to 12 hours, equivalent to one shift of the production line. For example, yellow fluorescent lamps and yellow LEDs that filter out wavelengths below 500 nm can be used. It should be noted that filling the cylinder can also be performed by the resin manufacturer or the manufacturer of the device for spraying the UV-curable resin containing the soft magnetic material, and the resin can be delivered to the party spraying the resin onto the substrate.
[0200] By using a light-curing resin, the heating required for curing resins containing soft magnetic materials, as previously done with thermosetting resins, is eliminated. Since a cooling process is also unnecessary besides heating, energy efficiency is improved. Furthermore, while thermosetting requires curing times ranging from tens of minutes to several hours, light-curing resins cure within seconds of light exposure, thus shortening the curing time. Additionally, with conventional thermosetting resins, workers risk burns or inhalation of solvents volatilized during heating and byproducts released into the gaseous environment. Light-curing resins, being solvent-free, eliminate the risk of inhaling solvents and reaction products during curing. Moreover, by covering the light source and having workers wear protective gear, radiation exposure can be easily prevented even if the light source is ultraviolet. These advantages are achieved through the use of light-curing resins.
[0201] <Implementation Method 6: Magnetic Body Installation Process: Ejection Step>
[0202] The "spraying step" is a step in which the filled light-curing resin containing soft magnetic material is sprayed onto the substrate through multiple spray windows located at the front end of the cylinder until it penetrates to the back of the substrate. Figure 5 This represents an example of multiple ejection windows located at the front end of the cylinder block. Figure 5 In the example, there is one hole in the center, and multiple holes are set around it in a double circle. 1mm).
[0203] The reason for spraying from multiple ejection windows is to easily form a magnetic layer over the required large area on the substrate surface. While spraying more resin from a single ejection window results in thickness, it is difficult to spread across the substrate and form a narrow area compared to spraying from multiple ejection windows.
[0204] A cylinder filled with a photocurable resin containing a soft magnetic material is brought close to the surface of a substrate. The photocurable resin containing the soft magnetic material is ejected from an ejection window on the substrate-side surface of the cylinder (the front end of the cylinder). The ejection volume is determined by the pressure applied to the photocurable resin containing the soft magnetic material inside the cylinder and the duration of pressure application. Ideally, the resin should be ejected to the extent that it penetrates to the back side of the substrate, but penetration to more than 1 / 2 the thickness of the substrate is also possible. Most preferably, it should penetrate to more than 2 / 3 the thickness of the substrate.
[0205] The surface of the substrate onto which the photocurable resin containing a soft magnetic material is sprayed can be the mold-side surface when mounted on the mold in the foam pad forming process, or the surface away from the mold. If the resin is sprayed onto the mold-side surface to form a magnetic layer, it can be placed closer to the magnet mounted on the mold. Forming the magnetic layer on the mold-side surface enhances the attraction between the magnet and the magnetic layer compared to forming it on the surface away from the mold. When the magnetic layer is mounted on the side away from the mold, the substrate is sandwiched between the magnetic layer and the magnet when attracted to it, and the substrate surface near the magnetic layer may deform. When the foam pad is removed from the mold after formation, the thickness of the base material near the magnetic layer may spring back and bulge slightly, deviating from the desired shape.
[0206] <Implementation Method 6: Magnetic Body Installation Process: Interval Inspection Step>
[0207] The “gap inspection step” is a step of inspecting the gaps between adjacent photocurable resin patterns containing soft magnetic materials that are ejected from adjacent ejection windows and adhered to the surface of the substrate.
[0208] After the spraying step, move the cylinder away from the substrate. Because it is from... Figure 5 The cylinder shown has multiple ejection windows that spray out resin, and the photocurable resin containing a soft magnetic material adheres to the substrate surface in a pattern shape that reflects the arrangement of the ejection windows. The spacing between such adjacent resin patterns is measured. The spacing between the resins is determined by the distance between the ejection window at the front end of the cylinder and the substrate surface, as well as the amount of resin ejected. Figure 6 A cross-sectional schematic diagram, and Figure 8The photographs and diagrams showing the resin pattern after spraying are examples of appropriate spraying amounts. The area corresponding to the spraying window has a "mountain" of sprayed resin, with the base of the mountain penetrating and extending into the substrate surface. Figure 7 The example shown in the cross-sectional schematic diagram is an example of excessive ejection volume, where the resin patterns ejected from adjacent ejection windows are connected.
[0209] use Figure 9 A cross-sectional schematic diagram of the resin pattern on the substrate surface after spraying is provided to illustrate an example of "interval". It can be the distance d1 between adjacent resin patterns where the resin is not adhered to or impregnated on the substrate surface (or whether such substrate surfaces are visible between the resin patterns), or the horizontal distances d2 and d3 at positions representing a predetermined proportion of the resin height (e.g., 90%, 10%). Alternatively, the interval can also be determined by measuring the half-value width d4 of the sprayed resin pattern. This is because the vertex position of the sprayed resin corresponds to the position of the spraying window and is approximately fixed regardless of the spraying conditions. Therefore, instead of the interval between resin patterns, the half-value width of the sprayed resin pattern (the width of the resin pattern at a position half the height from the substrate surface to the vertex) can be measured and subtracted from the interval of the spraying window to obtain the interval between the resin patterns. This example distance can be checked using a measuring instrument.
[0210] As an example of intervals, such as Figure 8 As shown in the schematic diagram on the right, the distance d1 or d1' between adjacent photocurable resin patterns containing soft magnetic materials (or the unattached or resin-impregnated substrate surfaces between adjacent resin patterns) can be measured, or the presence or absence of such gaps can be visually inspected. In the case of a simple visual inspection, for example... Figure 8 When both the gaps d1 and d1' between adjacent resins shown in the diagram on the right disappear, it is determined that the spray volume is too large and exceeds the upper limit. When the gap d" between the resin pattern sprayed from the central spray window and the adjacent outer spray window (or the substrate surface that is not adhered to or impregnated with resin) can be visually confirmed, it is determined that the spray volume is too small and falls below the lower limit. In cases where the spray volume is determined to exceed the upper limit or fall below the lower limit, it is used, for example, in a manner that is determined as NG in the good or bad determination step described later.
[0211] The interval inspection step can be performed either before or after the sprayed light-curing resin containing soft magnetic material has been cured.
[0212] <Implementation Method 6: Magnetic Body Installation Process: Determination of Quality>
[0213] The "Good or Bad Judgment Step" is a step that determines the goodness or badness of the sprayed product through an interval inspection step.
[0214] If, during the interval inspection step, the distance between the sprayed and adhered light-curing resin containing soft magnetic material to the substrate surface is greater than the specified value, the spray volume is below the lower limit, resulting in insufficient magnetic attraction to the mold and potential failure to adhere to the mold. This is considered poor spraying and is deemed defective. Conversely, if the spray volume exceeds the upper limit as gaps disappear, although adhesion to the mold is sufficient, the amount of light irradiated for curing (cumulative light intensity) is insufficient, potentially leaving uncured portions. Furthermore, spraying more than the required amount increases manufacturing costs. Therefore, this is also deemed defective. The determination of good or bad quality can be based on the numerical value of the interval measurement results, or it can be performed by visually inspecting the presence or absence of gaps between adjacent sprayed resin patterns, as described above. When performing the former interval measurement, the determination function can be integrated into the measuring device for simultaneous measurement. Alternatively, artificial intelligence can be used to determine the presence or absence of gaps between resin patterns sprayed onto the substrate surface through pattern recognition.
[0215] If the spray volume is below the lower limit, additional light-curing resin containing soft magnetic material can be sprayed manually. If the spray volume is above the upper limit, additional light can be applied for curing; if the resin is still in the pre-curing stage, a portion can be removed.
[0216] When a good or bad quality determination step is performed after the sprayed photocurable resin containing soft magnetic material has cured, it is preferable to not only determine the result based on the interval inspection step, but also to determine the appearance (shape, thickness distribution, presence or absence of cracks, presence or absence of foreign matter, etc.) of the magnetic layer formed on the substrate surface.
[0217] <Effects of Implementation Method 6>
[0218] By means of the method for forming a photocurable resin containing a soft magnetic material on a substrate according to Embodiment 6, it is possible to check the spacing of the resin adhering to the ejection substrate, determine the appropriate ejection amount, and manage the ejection process.
[0219] <Summary of Embodiment 7> Primarily refers to claim 7
[0220] Implementation Method 7: By specifying the specifications of the substrate (material, thickness, weight per unit area), a good magnetic layer is formed by using a photocurable resin containing a soft magnetic material sprayed onto the surface of the substrate.
[0221] <Implementation Method 7: Structure>
[0222] The substrate of Embodiment 7, which is based on Embodiment 6, is a nonwoven fabric made of fibers containing polyester, and its material, thickness, and weight per unit area are as follows.
[0223] <Effective Implementation 7: Substrate>
[0224] The "substrate" in Embodiment 7, based on Embodiment 6, is a nonwoven fabric composed of polyester fibers, with a thickness of 0.5 mm or more and 50 mm or less, and a weight per unit area of 50 g / m². 2 Above and 200g / m 2 The following range of nonwoven fabrics.
[0225] <Implementation Method 7: Substrate: Non-woven fabric>
[0226] When using a UV-curable resin that cures under ultraviolet light, the substrate can be a nonwoven fabric made of polyester fibers. Polyester fibers are composed of polymers with aromatic rings, exhibiting high molecular absorption coefficients for ultraviolet light and excellent UV shielding properties. While also influenced by the specifications of the fabric using polyester fibers, the UVA (wavelength 315-400 nm) transmittance of polyester fibers is generally around 10-20%. Therefore, as in Embodiment 8 described later, when light is irradiated from the back of the substrate, the light will not reach the vicinity of the substrate surface or the surface of the substrate containing the UV-curable resin with the soft magnetic material beyond what is necessary, thus preventing the resin on the substrate surface from curing.
[0227] <Implementation Method 7: Substrate: Thickness of nonwoven fabric>
[0228] The thickness of the nonwoven fabric used as the substrate is in the range of 0.5 mm to 50 mm. In the case of automotive seats, it is 1 to 5 mm, preferably 1 mm to 3 mm, and more preferably 1.5 mm to 2.5 mm. For automotive seats, insufficient thickness results in insufficient strength. If it is too thick, it becomes difficult to follow the shape of the mold used to form the foam pad; therefore, the above range is appropriate. The thickness of the nonwoven fabric used as the substrate for cushioning components with complex shapes, such as automotive seats, is within the above range, but if used for other applications (e.g., sound insulation materials, heat insulation materials, or entryway mats used in nonwoven fabric monomers with magnetic layers), a thickness of 10 to 50 mm is appropriate.
[0229] <Implementation Method 7: Substrate: Weight per unit area of nonwoven fabric>
[0230] The area weight of nonwoven fabric is 50 g / m² when the thickness is 2 mm. 2 ~200g / m 2 Preferably 100g / m 2 ~200g / m 2 More preferably 120~160g / m 2If the thickness is the same, but the weight per unit area is small, it can be considered a nonwoven fabric with a coarser mesh, resulting in weaker strength. If the weight per unit area is small, when the photocurable resin containing soft magnetic material is further sprayed onto the substrate surface, it may excessively penetrate the nonwoven fabric and reach the back of the substrate, potentially adhering to the stage of the spraying device and becoming contaminated. Conversely, if the weight per unit area is too large, the rigidity of the nonwoven fabric becomes too high, making it difficult to follow the shape of the mold; therefore, the above range is appropriate. When used as a substrate for foam pads in car seats, if the weight per unit area is too large, the permeability of gases during foaming, such as urethane resin, may further deteriorate.
[0231] <Effects of Implementation Method 7>
[0232] By using the nonwoven fabric of Embodiment 7 as a substrate, a photocurable resin containing a soft magnetic material can be well sprayed onto the surface of the substrate to form a magnetic layer.
[0233] <Summary of Embodiment 8> Mainly claims 8
[0234] The method for forming a photocurable resin containing a soft magnetic material on a substrate in Embodiment 8, which is based on any one of Embodiments 6 and 7, is configured such that, after the spraying step, curing light is irradiated from the back side of the sprayed resin, and then the spraying window is moved upward toward the resin to irradiate the resin with curing light.
[0235] <Implementation Method 8: Configuration>
[0236] use Figure 10 and Figure 11 This describes a method for forming a photocurable resin containing a soft magnetic material on a substrate, based on either Embodiment 6 or Embodiment 7, in Embodiment 8. Figure 10 Middle Mark As shown, the forming method of Embodiment 8 is configured to include, in addition to the forming method of Embodiment 6, an irradiation step, a retraction step, and a curing step after the spraying step. Therefore, only the irradiation step, the retraction step, and the curing step will be described below. It should be noted that in the following description, the additional irradiation step, the retraction step, and the curing step are configured to be performed between the spraying step and the interval inspection step, but it may also be configured to be performed after the interval inspection step or the good / bad determination step. In this case, the same effect can also be obtained.
[0237] <Implementation Method 8: Irradiation Step>
[0238] The “irradiation step” is a step after the spraying step in which curing light is irradiated from the back side of the photocurable resin containing a soft magnetic material that has been sprayed onto the substrate.
[0239] Figure 11 The leftmost diagram is an example of the spraying process. A light-curing resin (1132) containing a soft magnetic material is sprayed from the cylinder (1131) through the spraying window onto the surface of the substrate (1105). Figure 11 The central diagram illustrates an example of the irradiation process. UV light is emitted from a UV-LED light source (1134) through the substrate and directed onto the back of the ejected resin. Figure 11 In this embodiment, the stage (1133) where the cylinder (1131) and the substrate (1105) meet is missing, and a UV-LED light source (1134) is provided. Alternatively, a plate-shaped component can be provided at the missing portion of the stage to allow curing light for a photocurable resin containing a soft magnetic material to pass through. By configuring it to the same height as the surface of the stage that contacts the substrate, when the resin contacts the substrate from the ejection window at the front end of the cylinder and downward force is applied, significant downward bending of the substrate can be prevented. When UVA is used as the curing light, and in the case of a resin that is primarily cured with light at wavelengths around 365nm to 385nm, the plate-shaped component can be made of quartz glass or flat panel display glass with high transmittance from wavelengths in the visible light region to those wavelengths. It should be noted that in Embodiment 9 described later, when using… Figure 13 The same applies to the explanation.
[0240] When a light source is sprayed onto a substrate surface without irradiating the back side of the light-curing resin containing a soft magnetic material, and then the spray nozzle is retracted vertically upwards towards the resin, poor wettability or adhesion between the resin and the substrate surface results in most of the sprayed resin adhering to the spray nozzle and moving away from the substrate surface. Therefore, conventionally, instead of retracting vertically, a slight upward or horizontal movement is made before retracting vertically upwards to increase the contact area between the sprayed resin and the substrate surface, preventing it from adhering to the spray nozzle. However, this retraction method involves so-called "scraping" the resin sprayed through multiple spray nozzles onto the substrate surface, filling the gaps between the sprayed resin. Therefore, it is impossible to inspect the sprayed resin pattern and determine if the spray volume is within the normal range. Instead, the spray volume must be determined by measuring the cured resin using a ruler and stylus height difference gauge after the sprayed resin has cured, which is not a simple method.
[0241] After the ejection step, before the ejection window retracts, the curing light (e.g., ultraviolet light) irradiating the back side of the resin ejected onto the substrate is not intended to completely cure the resin, but rather to cure at least a portion of the resin that has penetrated into the substrate or the resin near the substrate surface, leaving the ejected resin on the substrate surface. By curing at least a portion of the resin that has penetrated or contacted the substrate, the resin can adhere to the ejection window without moving away from the substrate surface, even if the ejection window is retracted vertically. Even if the ejection window is retracted vertically upwards, the shape of the ejected resin is not disrupted, thus allowing the spacing of the resin corresponding to each ejection window to be measured in the subsequent interval inspection step.
[0242] In the irradiation step, the amount of curing light irradiated from the back is 10-20% of the cumulative light amount required for complete resin curing. If too much light is used, curing begins on the substrate surface. If even more light is used, the resin near the ejection window also begins to cure, and the opening of the ejection window narrows or becomes blocked. The above range is appropriate considering the transmittance of the nonwoven fabric or the like constituting the substrate.
[0243] <Implementation Method 8: Retreat Steps>
[0244] The "retreat step" is a step that, after the irradiation step, causes the ejection window to retract upwards toward the light-curing resin containing the soft magnetic material.
[0245] As described above, without performing the conventional irradiation step, instead of retracting vertically, the resin is moved slightly upwards or horizontally, and then retracted vertically upwards. This increases the contact area between the sprayed resin and the substrate surface, preventing it from adhering to the spray window. By using a photocurable resin as the polymerization raw material, and with an irradiation step, the spray window can be retracted upwards without damaging the shape of the resin sprayed onto the substrate surface (without changing the spacing of the resin in contact with the substrate). The retraction direction is most preferably vertically upwards from the location close to the substrate surface where the resin is sprayed.
[0246] <Implementation Method 8: Curing Step>
[0247] "Cure step" is the step of irradiating the light from above and / or below onto the substrate with a light source containing a soft magnetic material, after the retreat step. Figure 11 The rightmost diagram is an example of the curing process.
[0248] In the curing step, curing light is used to ensure complete curing of the resin sprayed onto the substrate surface. The curing light varies depending on the type of UV-curable resin used; a representative example is the use of a combination of UV lamps or UV LEDs for UV-curable resins. Figure 11In the example shown in the right figure, UV light is irradiated only from the surface side of the resin as the curing light, but it is also possible to use only the light source for curing light on the back side used in the irradiation step, i.e., a UV-LED light source, or to irradiate it from both sides to cure it.
[0249] Using both upper and lower curing light sources increases the amount of light emitted per unit time, thus shortening the curing time. The curing time of light-cured resins is only a few seconds, which is significantly shorter than the several minutes to tens of minutes (and even hours for some types) required for thermosetting resins.
[0250] <Effects of Implementation Method 8>
[0251] The method for forming a photocurable resin containing a soft magnetic material on a substrate according to Embodiment 8 allows the ejection window to be moved away from the substrate (receded) without the ejected photocurable resin containing a soft magnetic material adhering to it. Furthermore, after such retraction, the spacing between the resins can be measured, and the ejection amount can be managed.
[0252] <Summary of Embodiment 9> Primarily refers to claim 9
[0253] The method for forming a photocurable resin containing a soft magnetic material on a substrate according to Embodiment 9 further includes an overflow pressing step of pressing the front end of a cylinder onto the substrate while the resin is overflowing from the spray window before the spray window is cured onto the substrate.
[0254] <Implementation Method 9: Structure>
[0255] Figure 12 and Figure 13 This refers to the formation method of Embodiment 9, which is based on the method for forming a photocurable resin containing a soft magnetic material on a substrate according to any one of Embodiments 6 to 8. The formation method of Embodiment 9, compared to the formation method of Embodiment 8, further includes an overflow pressing sub-step in the ejection step. Since steps other than the overflow pressing step have already been described, only the overflow pressing step will be described below. It should be noted that the same effect can be obtained based on any one of Embodiments 6 and 7.
[0256] <Implementation Method 9: Overflow Press Step>
[0257] The “overflow extrusion sub-step” is a sub-step in the ejection step in which a light-curing resin containing a soft magnetic material overflows from the ejection window before the ejection window is lowered toward the substrate, and then the front end of the cylinder is pressed onto the substrate in this state.
[0258] Figure 12This is a flowchart illustrating the magnetic material mounting process (the method for forming a photocurable resin containing a soft magnetic material on a substrate according to this application) of Embodiment 9, based on Embodiment 8. In the ejection step, an overflow pressing step is performed.
[0259] Figure 13 This is a schematic diagram illustrating each step. There are five diagrams arranged in a row. The leftmost diagram shows the state after the filling step is completed, with the cylinder body set on the ejection device and the substrate (1305) placed on the stage of the ejection device. The cylinder body (1331) of the ejection device and... Figure 11 Unlike other parts, the UV-LED light source (1334) on the upper side of the substrate is set in the part of the cover that is opened and closed on the front end side of the housing (1336) containing the cylinder (1331). Figure 13 also with Figure 11 Similarly, a stage portion corresponding to the substrate that comes into contact with the sprayed resin is lacking. Alternatively, this portion can be configured such that a plate-shaped component, such as quartz glass, which transmits light for curing, is provided as described above, preventing the substrate from bending downwards when the resin comes into contact with the substrate as described above.
[0260] Figure 13 The second figure from the left shows the state in which the photocurable resin containing a soft magnetic material overflows from the spray window during the spraying and overflow pressing steps. A predetermined amount is sprayed from the spray window, and the state is maintained with the photocurable resin containing a soft magnetic material adhering to the front end of the cylinder. If the viscosity and / or thixotropy is low, the sprayed resin will drip directly onto the substrate surface. With the cover at the front end of the housing (1336) of the cylinder (1331) open, the front end of the cylinder is lowered from the cover and pressed against the substrate surface (see reference). Figure 13 (See the diagram in the center). By pre-filling a predetermined amount, changes in the distance to the front of the cylinder due to unevenness on the substrate surface can be prevented, and the spray volume varies for each substrate.
[0261] Figure 13 The fourth figure from the left illustrates the irradiation process. With the front end of the cylinder pressed down, curing light is irradiated from the back of the ejected photocurable resin containing a soft magnetic material (in...). Figure 13 In the example, UV light (1335) is used to cure at least a portion of the resin that has penetrated into the nonwoven fabric serving as the substrate, or near the surface of the substrate.
[0262] Figure 13 The rightmost diagram illustrates the curing step. The cylinder is retracted vertically upwards towards the resin, the cap at the front of the cylinder is closed, and UV light for resin curing is irradiated from a UV-LED mounted on the cap. After the resin has cured, the spacing between resin particles is checked to determine if it is satisfactory, and the process ends. Alternatively, the curing step can also be configured so that curing light is also irradiated from a UV-LED light source on the lower side.
[0263] Figure 13 The cylinder shown, which ejects a photocurable resin containing a soft magnetic material, can be configured such that moving the cylinder relative to its housing to an ejection position opens the cover at the front end of the housing. Conversely, moving the cylinder relative to the housing upwards (away from the substrate surface) closes the cover at the front end of the housing. For example, a gear (pinion) can be provided in a portion of the cover's rotation axis relative to the housing, rotating synchronously with the cover, and engaged with a rack (a plate with teeth of the same shape equally spaced) located next to the cylinder. With this configuration, the cover can be opened or closed by moving the cylinder up and down.
[0264] <Effects of Implementation Method 9>
[0265] By means of the method for forming a photocurable resin containing a soft magnetic material on a substrate according to Embodiment 9, the amount of the resin sprayed onto the substrate can be kept constant.
[0266] <Implementation Method 10 Overview>
[0267] In the spraying step of the method for forming a photocurable resin containing a soft magnetic material on a substrate according to Embodiment 10, the weight of the photocurable resin containing a soft magnetic material sprayed onto the substrate is in the range of 0.10 g to 0.25 g.
[0268] <Implementation Method 10 Configuration>
[0269] In the spraying step of the method for forming a photocurable resin containing a soft magnetic material on a substrate in Embodiment 10, which is based on any one of Embodiments 6 to 9, the weight of the photocurable resin containing a soft magnetic material sprayed onto the substrate is in the range of 0.10 g to 0.25 g.
[0270] In the spraying step, the weight of the resin sprayed onto the substrate is 0.1 g to 0.25 g. 0.10 g to 0.15 g is more preferred, and 0.125 g is most preferred. If the spraying amount is too small, the attraction force to the magnet becomes insufficient. If the spraying amount is too large, when spraying onto the substrate, adjacent resin patterns on the substrate surface may come into contact with each other and become integrated, making it possible to not be able to measure the distance between the resin patterns. When the spraying amount is 0.25 g or more, as in estimating the aperture ratio in Embodiment 1, the soft magnetic powder mixed in the resin hinders the transmission of curing light, resulting in insufficient cumulative light required for curing inside the resin, potentially leading to incomplete curing. Therefore, the upper limit is 0.25 g.
[0271] By setting the resin to the above range, when performing a single spraying step on the substrate surface, the resin contains 0.05g to 0.1875g of soft magnetic material, which can form a magnetic material layer sufficient to be attracted to a magnet provided in the mold.
[0272] <Effects of Implementation Method 10>
[0273] In the method for forming a photocurable resin containing a soft magnetic material on a substrate according to Embodiment 10, by specifying the amount of the sprayed resin, it is possible to prevent the formed magnetic layer from cracking or being damaged when the substrate is bent, and thus it can be well implemented when performing the overflow pressing step.
[0274] <Effect>
[0275] This invention relates to a soft magnetic material powder (e.g., iron) mixed in an adhesive, which can produce a magnetic layer that also ensures elasticity, and can provide a range of ratios in which the substrate to which the magnetic layer is formed can be sufficiently attracted to a magnet. Furthermore, it provides a method for forming a photocurable resin containing a soft magnetic material on a substrate, wherein when the photocurable resin containing the soft magnetic material is sprayed onto the substrate, a portion of the adhesive adhering to the substrate is cured before the spraying window is moved away from the substrate, thus preventing damage to the resin spraying shape, and allowing appropriate management of the spraying amount based on checking the distance between the sprayed resin particles.
[0276] Explanation of reference numerals in the attached figures
[0277] 1105: Substrate; 1131: Cylinder; 1132: Photocurable resin containing soft magnetic material; 1133: Stage; 1134: UV-LED light source; 1135: UV light.
Claims
1. A light-curable resin containing a soft magnetic material, It comprises polymerization raw materials, crosslinking agents, photoinitiators and soft magnetic powder, wherein the polymerization raw materials comprise at least urethane oligomers having acryloyl groups and / or epoxy groups, and the soft magnetic powder comprises 50% to 75% by weight.
2. The photocurable resin containing a soft magnetic material according to claim 1, wherein, The crosslinking agent is 2-hydroxypropyl methacrylate.
3. The photocurable resin containing a soft magnetic material according to claim 1 or 2, wherein, It further contains reaction-promoting additives.
4. The photocurable resin containing a soft magnetic material according to claim 1 or 2, wherein, The viscosity of the polymer raw materials contained in the resin before photocuring was measured using a type B viscometer, and was 1,000 to 500,000 millipascal-seconds at a rotation speed of 0.6 rpm or less.
5. The photocurable resin containing a soft magnetic material according to claim 4, wherein, The viscosity of the polymer raw materials contained in the resin before photocuring was measured using a type B rotational viscometer. The viscosity at 6 rpm was above 40,000 mPa·s and below 44,000 mPa·s, and the viscosity at 12 rpm was above 30,000 mPa·s and below 34,000 mPa·s.
6. A method for forming a photocurable resin containing a soft magnetic material on a substrate, comprising: The filling step involves filling the cylinder with the light-curing resin containing a soft magnetic material as described in claim 1. In the spraying step, the light-curing resin containing soft magnetic material is sprayed onto the substrate through multiple spray windows located at the front end of the cylinder until it penetrates to the back of the substrate. The spacing inspection step involves checking the spacing between adjacent photocurable resin patterns containing soft magnetic materials that are ejected from adjacent ejection windows and adhere to the surface of the substrate; and The good or bad determination step is to determine the good or bad quality of the sprayed product through an interval inspection step.
7. The method for forming a photocurable resin containing a soft magnetic material on a substrate according to claim 6, wherein, The substrate is a nonwoven fabric composed of polyester fibers, with a thickness of 0.5 mm or more and 50 mm or less, and a unit area weight of 50 g / m². 2 Above and 200g / m 2 The following range of nonwoven fabrics.
8. The method for forming a photocurable resin containing a soft magnetic material on a substrate according to claim 6 or 7, wherein, Following the ejection step, it further includes: The step of irradiating the back side of a photocurable resin containing a soft magnetic material sprayed onto a substrate with curing light; and The retraction step, following the irradiation step, involves retracting the ejection window upwards toward the light-cured resin containing the soft magnetic material. Following the retreat step, there is a curing step in which a light-curing resin containing a soft magnetic material, ejected from the substrate, is irradiated with curing light from above and / or below.
9. The method for forming a photocurable resin containing a soft magnetic material on a substrate according to claim 6 or 7, wherein, The ejection step includes an overflow pressing step in which, before the ejection window is lowered toward the substrate, a light-curing resin containing a soft magnetic material overflows from the ejection window, and then the front end of the cylinder is pressed onto the substrate in this state.
10. The method for forming a photocurable resin containing a soft magnetic material on a substrate according to claim 6 or 7, wherein, In the spraying step, the weight of the light-curable resin containing soft magnetic material sprayed onto the substrate is in the range of 0.10 g to 0.25 g.
Citation Information
Patent Citations
Seat pad and manufacturing method thereof
JP2016036463A